Frustration phenomena in Josephson point contacts between single-band and three-band superconductors: III Международный семинар по микроконтактной спектроскопииХарьков, Украина, 8–11 сентября 2014 г. - Yerin, Y.S.; Omelyanchouk, A.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
Within the formalizm of Usadel equations the Josephson effect in dirty point contacts between single-band and three-band superconductors is investigated. The general expression for the Josephson current, which is valid for arbitrary temperatures, is obtained. We calculate current-phase relations for very low temperature and in the vicinity of the critical temperature. For three-band superconductors with broken time-reversal symmetry (BTRS) point contacts undergo frustration phenomena with different current-phase relations, corresponding to φ-contacts. For three-band superconductors without BTRS we have close to sinusoidal current-phase relations and ab-sence of the frustration, excepting the case of very low temperature, where under certain conditions two ground states of the point contact are realized. Our results can be used as the potential probe for the detection of the possible BTRS state in three-band superconducting systems.